REVISITING THE ROLE OF ICT IN DEVELOPMENT - G. Harindranath and Maung K. Sein (Proceedings of the 9th International Conference on Social Implications of Computers in Developing Countries, Sao Paulo, Brazil, May 2007, 2007)
It is now widely accepted that Information and Communication Technologies (ICT) have an important role in national development. However, the nature of the link between the two remains unclear. Much of this state is due to lack of clarity on how ICT is conceptualized in this context. While some conceptual frameworks have been proposed, they lack important aspects that can give a more comprehensive picture. In this paper, we attempt to further clarify how ICT is conceptualised in development. Using secondary data, we evaluate two conceptual frameworks that bring together the range of views of ICT, their manifold impacts, and the assumptions and perspectives of the range of actors in any given development project that involves ICT. The specific case we examine is an e-Government initiative called e-Seva in the Indian state of Andhra Pradesh. We found that even when using the two frameworks in conjunction, many aspects of the ICT initiatives remain unclear. We suggest ways of combining different frameworks to provide a sharper lens to give us a better understanding of why ICT for development projects may fail or succeed